Characterization of Interferon Regulatory Factor 4 (IRF4) target genes in melanoma cell lines - Yılmaz, Erdem. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
IRF4 is a critical transcription factor in the development and function of immune cells, and additionally, it is deregulated in certain myeloid and lymphoid malignancies. Un-til recently, IRF4 expression was thought to be restricted to immune cells; however, recent studies showed its expression in non-immune cells, such as melanocytes. We observed that certain human melanoma cell lines also have IRF4 expression and its expression appears critical for the viability of melanoma cells as in the case of B-cell origin malignancies. As there is a relative lack of understanding about IRF4 in melanoma we set out to identify its downstream transcriptional target genes using high-throughput sequencing in order to identify the pathways and biological processes IRF4 regulates in human melanoma cells. For this purpose, as a first step, we determined the optimal conditions for the expression profiling analysis. Then, we compared gene expression profiles of IRF4 knock down cells with control by high-throughput cDNA sequencing (RNA-seq). We analyzed the sequenc-ing data via a bioinformatics pipeline to find the significantly differentially expressed genes upon IRF4 knock-down. We validated the results of RNA-seq by real-time semi-quantitative polymerase chain reaction for selected genes. Subsequently, we performed characterization of enriched functional classes of the differentially expressed genes by gene enrichment analysis of gene ontology terms. Our analysis indicates that IRF4 pre-dominantly activates genes related to proliferation, and represses genes linked with lipid metabolism in human melanoma cell lines. Additionally, following leads from the results of RNA-seq analysis we showed the role of IRF4 on the transcriptional regulation of a prominent melanocyte master regulator and a key survival pathway in certain melanoma cell lines.
Keywords: Interferon.